The invasive red king crab (Paralithodes camtschaticus): Mortality, individual growth and dispersal in Norwegian waters - Windsland, Kristin (UiT The Arctic University of Norway, 2014)
The papers of this thesis are not available in Munin: 1. Windsland, K., Hvingel, C., Nilssen, E. M., Sundet, J. H.: 'Evaluation of von Bertalanffy growth curves for the introduced red king crab (Paralithodes camtschaticus) in Norwegian waters', Fisheries Research (2013), vol. 145:15-21. Available at http://dx.doi.org/10.1016/j.fishres.2013.03.003 2. Windsland, K., Hvingel, C., Nilssen, E. M., Sundet, J. H.: 'Dispersal of the introduced red king crab (Paralithodes camtschaticus) in Norwegian waters: a tag-recapture study', ICES Journal of Marine Science (2014), online before print. Available at http://dx.doi.org/10.1093/icesjms/fst241 3. Windsland, K.: 'Total and natural mortality of red king crab (Paralithodes camtschaticus) in Norwegian waters: Catch curve analysis and indirect estimation methods' (manuscript). To improve local economy, the red king crab (Paralithodes camtschaticus) was introduced to the Barents Sea by Soviet scientists in the 1960s. Adapting well to the new environment, the growing population gradually invaded new areas along the coast of northern Norway. The red king crab has become a valuable marine resource but as an introduced species, it is also a potential threat to the ecosystem. To meet the management goals, more knowledge about the growth, mortality and dispersal of the species is essential. This thesis attempts to provide this knowledge. In paper I, we developed Bayesian hierarchical models to estimate growth parameters of the von Bertalanffy growth function using tag-recapture data. Allowing for individual variability led to increased precision in estimated lengths and to more realistic values for the growth parameters. The length-at-relative age of small males were overestimated, while those of small females were not. This is believed to be due to differences in growth patterns after maturity. In paper II, we explored the dispersal behaviour and extent of dispersal of red king crab in Norwegian waters. The results indicated that the range expansion of this species is a result of ...